Reaksi Usaha Mikro Merespon Insentif Pajak dalam Investasi dan Inovasi - Kristiana, Deranika Ratna; Kristianti, Ika Puspita (E-Jurnal Akuntansi, 2023)
The purpose of this study is to identify micro-entrepreneurs who take advantage of tax incentives and MSME actors who invest in loan instruments to increase their business capital or innovate products to attract public attention for the continuity of their business. This research uses explanatory method; the testing hypothesis is formulated using descriptive qualitative data by distributing online questionnaires to micro-entrepreneurs. The total data taken was 84 respondents. The results of the study show that the reaction of micro-entrepreneurs to government policies in the final PPh has no impact on the product innovation of micro-entrepreneurs and investment in loan instruments for micro-entrepreneurs has an impact on product innovation of MSME actors. The final PPh DTP policy has implications for the reaction of micro-entrepreneurs in addressing this policy. Fiscal policy needs to be disseminated to the public, especially micro businesses. Exploration of the concept of fiscal policy refers to the latest regulations governing the DTP final PPh policy. Keywords: Fiscal Policy; Tax Incentives; Responds Of Small Enterprises; Loan Instrument Investment; Product Innovation